Locust lane eaudiobook A novel. - Amidon, Stephen (Macmillan Audio, 2023)
"This is a plot that uncovers many secrets, and Campbell treats them all evenhandedly with no hints that give away the identity of the murderer before the mystery's reveal."- AudioFile For fans of Mystic River by Dennis Lehane and Little Fires Everywhere by Celeste Ng , Audible Hall of Fame narrator Cassandra Campbell delivers an electrifying performance of Stephen Amidon's Locust Lane, a taut and utterly propulsive story about the search for justice and the fault lines of power and influence in a seemingly idyllic town. On the surface, Emerson, Massachusetts, is just like any other affluent New England suburb. But when a young woman is found dead in the nicest part of town, the powerful neighbors close ranks to keep their families safe. In this searing novel, Eden Perry's death kicks off an investigation into the three teenagers who were partying with her that night, each a suspect. Hannah, a sweet girl with an unstable history. Jack, the popular kid with a mean streak. Christopher, an outsider desperate to fit in. Their parents, each with motivations of their own, only complicate the picture: they will do anything to protect their children, even at the others' expense. With a brilliantly woven, intricately crafted plot that gathers momentum on every page, this is superb storytelling told in terse prose—a dynamic listen that is both intensely gripping and deeply affecting. A Macmillan Audio production from Celadon Books.